If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9r + -5 = -59 Reorder the terms: -5 + 9r = -59 Solving -5 + 9r = -59 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 9r = -59 + 5 Combine like terms: -5 + 5 = 0 0 + 9r = -59 + 5 9r = -59 + 5 Combine like terms: -59 + 5 = -54 9r = -54 Divide each side by '9'. r = -6 Simplifying r = -6
| 6x+3=-x+80 | | (-17)+5= | | 2x-15=44+8x | | -18-6x=27+3x | | 5-1/2(c-6)=4 | | x^4-2x^3-3x^2+2x+1=0 | | x^4-2x^3-3x^2+2x+3=0 | | 26=-1+(27x)3/4 | | 1/3x=42/3 | | 9x-5y= | | 4(1-4x)=-124 | | 2xy+2x= | | -3(5k+6)=102 | | 4(c+5)=8 | | 7x^2+31x+-20=0 | | k/3=9 | | 4lnx+28ln=20 | | 7(3-5r)=126 | | 6(6+5m)=186 | | 4ln(x+7)=20 | | 7+2n/2=10 | | -3+11=-2z+3(z-2) | | -2A+8A-18+5A=-A+14-5A+2 | | 4x^2-16x+80=113 | | 2x+8=4x+11 | | 5x^2-11x-2=0 | | 16x-4y=32 | | 6(2a+7)=102 | | 10x^2-11x-2=0 | | 98b^2=2 | | (6r-3)(8r-3)= | | x-7=2x-3 |